Cross-Cultural Perspectives on Intercultural Communication Competence. Issue 1 (2nd January 2016) - Barker, Gina G.
Abstract: This study examined the process of developing intercultural communication competence (ICC) with particular attention to cross-cultural differences in communication patterns. A qualitative approach involving 40 interviews with Americans living in Sweden and Swedes living in the US was employed in order to gain a nuanced, in-depth, and contextual understanding of how immigrants and expatriates experience the process. Several differences in verbal and nonverbal communication patterns between the two cultures emerged. The findings provide insights into how ICC is developed differently across cultures, as well as how the cognitive, affective, and behavioral components of ICC are interrelated and influenced by culture-specific aspects.